Flat no longer technology in the Post-COVID world (2020)
Even before the world faced a pandemic crisis, the bloom was already coming off the rose of globalization. Nowhere is this more true than in the hightechnology arena—an arena that had been at the forefront of breaking down barriers and transcending the traditional antagonisms between nations. Technology, commerce, and connectivity would move on apace regardless of what governments did or said. Fields such as telecommunications, computing, artificial intelligence (AI), and biotechnology have all benefited from the relatively open exchange of people and products since the Cold War ended. By the time the COVID-19 pandemic struck, the globalist system of technology commerce and research was already starting to fray. The United States was in the midst of using its semiconductor advantages to slow the spread of Chinese telecommunications infrastructure—efforts that would intensify after the outbreak. The COVID-19 crisis revealed the United States’ deep and disturbing dependence on China for key pharmaceuticals and medical equipment, sparking calls for more self-sufficiency and less reliance on foreign suppliers. The kind of globalism extolled by Thomas Friedman and others after the Cold War now looks much less inevitable—and attractive—in the wake of COVID-19.